2018
DOI: 10.1016/j.chest.2017.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Adoption Rate of Video-Assisted Thoracic Surgery for Lung Cancer Varies Widely in China

Abstract: are clinically undetectable (lanthanic): Hägerstrand and Linell 3 reported a sarcoidosis prevalence of $640/100,000 in a Swedish autopsy series of 6,706 cases, 10-fold the point prevalence estimated by mass chest radiographic (CR) screening in a Stockholm population. Reid 4 reported an autopsy incidence 10-fold that reported on Cuyahoga death certificates. Systematic CR screening increased ascertainment by > 3-fold vs symptomatic or incidental CR presentation. 5 The order of magnitude of CT vs CR screening in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In China, video-assisted thoracoscopic surgery (VATS), as a rational alternative to open thoracotomy, was increasingly used [156][157][158]. A retrospective study of 7,726 Chinese NSCLC patients found that VATS lobectomy was related to better perioperative outcomes in comparison with open lobectomy [159].…”
Section: Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…In China, video-assisted thoracoscopic surgery (VATS), as a rational alternative to open thoracotomy, was increasingly used [156][157][158]. A retrospective study of 7,726 Chinese NSCLC patients found that VATS lobectomy was related to better perioperative outcomes in comparison with open lobectomy [159].…”
Section: Surgerymentioning
confidence: 99%
“…It is recommended that regional lymph node dissection at least includes three hilar lymph node stations and three mediastinal lymph node stations [ 155 ]. In China, video‐assisted thoracoscopic surgery (VATS), as a rational alternative to open thoracotomy, was increasingly used [ 156 , 157 , 158 ]. A retrospective study of 7,726 Chinese NSCLC patients found that VATS lobectomy was related to better perioperative outcomes in comparison with open lobectomy [ 159 ].…”
Section: Treatmentmentioning
confidence: 99%
“…In recent years, minimally invasive procedure has developed rapidly and become as mainstream approach especially in thoracic surgery [12][13][14]. Improvements in equipment and technology have made it possible to perform minor and major pulmonary resections by complete VATS: such as lung biopsy, wedge resection, sleeve resection and even pneumonectomy.…”
Section: The Effectiveness and Feasibility Of Thoracoscopic Reoperationmentioning
confidence: 99%